Straightbred and composite progeny’s impact on cowherd economic performance - Blew, Darren (Kansas State University, 2016)
Crossbreeding has long been promoted as the preferred method of production for cow-calf producers. Unfortunately, crossbreeding can add complexity to maintain a consistent cowherd and can drive the need to purchase replacement females from outside the producer’s own herd. This has led some producers to pursue straightbreeding to provide their own supply of replacements and the opportunity to more narrowly select for individuals suited to a carcass quality grid marketing system. The subject of this thesis is a Red Angus based cowherd that breeds females to Red Angus sires in early parities. The same cowherd is bred to Simmental sires in later parities to produce a terminal F1 cross. It is the objective of this thesis to explore whether this operation’s straghtbred or crossbred calf crop provides an economic advantage to the other treatment. Mortality data were collected during pre-weaning for both steers and heifers. Mortality data were collected for steers during backgrounding and feedlot phases. Wean weights and feed conversion performance during the backgrounding phase was unavailable for use in this study. Feedlot and carcass data were captured for steers from both treatments. The straightbred treatment showed an advantage in carcass quality. The composite treatment showed a slight advantage in mortality cost during pre-weaning and feedlot phase, and a slight advantage in feed conversion and cost per pound of gain while in the feedlot. The composite treatment showed a significant disadvantage during the backgrounding phase. The primary advantage for the composite treatment was the difference in actual wean weights. This difference in wean weight carried over to a higher start weight during the feedlot phase. This was the driving factor in providing the composite group the economic advantage in this study and making it the more attractive production option.
Keywords: Cost-benefit analysis; Purebred; Crossbred; Cow-calf